A new green-coloured Lusitanipus Mauriès, 1978 from the Iberian Peninsula (Diplopoda: Callipodida: Dorypetalidae) - Gilgado, José Domingo; Martínez-Pillado, Virginia; Prieto, Carlos E. (European Journal of Taxonomy, 2020)
Recent samplings in cavities of the Iberian Peninsula led to the discovery of a new millipede species of the order Callipodida in one cave in the region of El Bierzo (León, Spain): Lusitanipus xanin sp. nov. In additional samplings (near that cave), more specimens of this new species were discovered in surface habitats. The species has various distinctive characteristics, such as its green colour, but the morphology of the gonopod has several similarities with that of Lusitanipus alternans (Verhoeff, 1893), indicating a close relationship between them. The diagnosis of the genus Lusitanipus Mauriès, 1978 has to be changed to accommodate the new species. The presence of crests in two different sizes is no longer a diagnostic character of the genus Lusitanipus, but of the species L. alternans. Lusitanipus xanin sp. nov. is the fourth species of the order Callipodida for the Iberian Peninsula, and the second species for the genus. Lusitanipus xanin sp. nov. seems to be an epigean but troglophile species.